Advanced cybersecurity in industrial systems: key strategies and frameworks to lead the transition to Industry 5.0 - Marin Bardales, Noe Humberto; Silva Florentini, Miryam Liliana; Paredes Morales, Ana Elizabeth; Correa Rojas, Liliana; Olivos Jimenez, Luis Marcelo; Coronado Farroñán, Williams; Arbulú Castillo, Julie Catherine (LACCEI, 2025)
Abstract – The research addresses the transition to Industry 5.0, highlighting emerging challenges in cybersecurity for industrial systems, especially in contexts of advanced cyber-physical systems and the integration of emerging technologies such as blockchain and quantum computing. It analyzes the impact of technologies such as 5G and IoT on the security of critical infrastructures, such as power grids and industrial control systems. The study also explores automation in security incident response and the implementation of advanced detection solutions based on AI, machine learning and deep learning. Finally, the paper emphasizes the importance of human-robot collaboration and the need to adapt to new vulnerabilities, proposing an updated conceptual framework for addressing cybersecurity challenges in Industry 5.0. This analysis provides a comprehensive view of current advances and gaps in industrial cybersecurity, suggesting key areas for future research and the development of more adaptive and effective solutions.